Profil pitiriasis versikolor di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari-Desember 2013 - Isa, Dwi Y.F.; Niode, Nurdjannah J.; Pandaleke, Herry E.J. (Universitas Sam Ratulangi, 2016)
Abstract: Pityriasis versicolor is a chronic superficial fungal disease caused by Malasezzia furfur. Pityriasis versicolor can infect the face, neck, trunk, upper arms, underarms, and groin. Pityriasis versicolor is characterized by scaly patches of fine white or dark, irregular to regular shapes, and clear to diffuse limits. However, pityriasis versicolor is generally asymptomatic, therefore, commonly people do not realize that they are infected by that fungi. This study aimed to determine the profile of pityriasis versicolor at Dermatovenereology clinic of Prof. Dr. R. D. Kandou Hospital from January to December 2013. This was a retrospective descriptive study based on the number of cases, sex, age, occupation, color of lesion, location of lesion, and type of treatment. The results showed that there were 36 cases of pityriasis versicolor, mostly were males (58.3%), age groups 15-24 years and 25-44 years (30.6%), and private workers (27.8 %). Most lesions were hypopigmentation (80.6%), located on the body area and the combination of the face, trunk, and extremities (38.9%). The most commonly prescribed treatment was topical antifungal therapy (77.8%). Keywords: pityriasis versicolorÂ Abstrak: Pitiriasis versikolor merupakan penyakit jamur superfisial kronik yang disebabkan oleh Malasezzia furfur. Pitiriasis versikolor dapat menginfeksi wajah, leher, badan, lengan atas, ketiak, dan lipat paha. Pitiriasis versikolor ditandai dengan adanya bercak-bercak bersisik halus berwarna putih atau gelap, bentuk tidak teratur sampai teratur, dan batas jelas sampai difus. Umumnya gejala pitiriasis versikolor asimtomatik sehingga terkadang penderita tidak menyadari telah terinfeksi penyakit tersebut. Penelitian ini bertujuan untuk mengetahui profil pitiriasis versikolor di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou periode Januari-Desember 2013. Jenis penelitian ini ialah deskriptif retrospektif berdasarkan jumlah kasus, jenis kelamin, umur, pekerjaan, warna lesi, lokasi lesi, dan jenis pengobatan. Hasil penelitian mendapatkan 36 kasus pitiriasis versikolor, terbanyak pada laki-laki (58,3%), kelompok usia 15-24 tahun dan 25-44 tahun (30,6%), dan pekerja swasta (27,8%). Lesi hipopigmentasi paling banyak ditemukan (80,6%) dengan lokasi lesi pada daerah badan dan kombinasi antara wajah, badan, ekstremitas (38,9%). Pengobatan yang paling sering diberikan ialah terapi antijamur topikal (77,8%).Kata kunci: pitiriasis versikolor